Numerical identification of the dynamic characteristics of structural units of designed machines - Ivanov, Vladimir Nikolaevich; Dombrovskij, Igor Viktorovich; Shevelev, Nikolay Alekseevich (Computational Continuum Mechanics, 2011)
A time-domain numerical method is proposed to identify the dynamic characteristics of structural units of designed machines at the stage of their testing. The method provides procedures for determining such vibration parameters as the number and values of natural frequencies and vibration logarithmic decrements, and such mathematical model parameters as the reduced rigidity and damping coefficients for force elements. The approach exploits the discrete samples of observations of the behavior of separate structural units. A variant of Prony’s method is used in combination with the algorithm of singular value decomposition of the observation matrix. The method is based on the assumption of the adequacy of solutions of linear homogeneous differential equations and the equivalent system of finite-difference equations of the same order. The results of field tests are compared with the predictions of the mathematical model of a certain mechanical system.